新加坡6-7岁英汉双语儿童汉语动词使用特征 ：以三个脚部动作动词和三个手部动作动词为例 = Characteristics of the Chinese language use by 6-7-year-old bilingual Singaporean children : examples from three foot and three hand action verbs in Chinese - 徐詠冰 Ser, Yong Bing (2019)
双语政策是新加坡教育的基石。英语是主要的教学媒介语，重在实用；华语 则是母语，重在传递文化。在2015年，新加坡推出了新的母语教材，定名为“欢乐 伙伴”。基于这长久以来所实行的双语政策以及新教材的推出，新加坡英汉双语儿 童的语言发展情况如何？我们可否通过检验某些儿童常用的词汇来跟踪和预测儿童 的语言发展？本研究采用了汉语的两组生活常用的身体动作动词中的近义词来考察 儿童的语言使用情况。两组近义词分别为脚部类动词中的“跑、逃、冲”以及手部 类动词中的“打、拍、投”。 本研究采用了六张图片来测试英汉双语儿童动词的使用特征。研究也通过动 画教导了儿童还未习得的脚部和手部动作动词，分别为“冲”和“投”。本研究也 采用了Gao(2016)的《新加坡双语儿童词汇发展家长报告表》作为问卷调查，了解 儿童的家庭与语言背景。通过分析30位6-7岁儿童在描述动作时所使用的词汇和句 类，本研究探讨了新加坡英汉双语儿童汉语动词的使用特征及影响语言发展的因素。Bilingual policy has been the cornerstone for the education system in Singapore. English as the main language for the teaching medium, emphasizing on practical usage; Chinese is learned as the Mother Tongue, with an emphasis on the passing down of Chinese culture. In 2015, a revised edition of teaching materials was debuted, named as “Huan Le Huo Ban” (Happy Companions). On the basis of the bilingual policy implemented long ago and the debut of new teaching materials, how is the state of Chinese language acquisition by Singapore bilingual children? Are we able to track and predict the state of Chinese language development in the children? The study investigated the use of Chinese language by the children through two sets of near-synonymous physical action verbs that are frequently used in real-life. An experiment was conducted with 30 children aged 6-7 using six pictures to illustrate two sets of near-synonymous physical action verbs that are foot action verbs “pǎo, táo, chōng” and hand action verbs “dǎ, pāi, tóu” to investigate the characteristics of Chinese language use by Singapore bilingual children. The like animation videos were used to teach the foot and hand action verbs “chōng” and “tóu” that were not yet acquired by the children. This study also used Gao’s (2016) “Parent Report Form for bilingual development studies in Singapore” as questionnaire to find out the family and language background of the children. Through the analysis of the words and sentence pattern used during the description of the actions by the children, the study evaluated the characteristics of the Chinese language use by Singapore bilingual children and the factors affecting their Chinese language development.